The efficacy and safety of venetoclax therapy in elderly patients with relapsed, refractory chronic lymphocytic leukaemia. (4th November 2019) - Eyre, Toby A.; Roeker, Lindsey E.; Fox, Christopher P.; Gohill, Satyen H.; Walewska, Renata; Walter, Harriet S.; Forconi, Francesco; Broom, Angus; Arumainathan, Arvind; Brander, Danielle M.; Allan, John N.; Schuster, Stephen J.; et al.
Summary: Elderly chronic lymphocytic leukaemia (CLL) patients treated outside of trials have notably greater toxicity with the Bruton's tyrosine kinase inhibitor ibrutinib compared to younger patients. It is not known whether the same holds true for the B‐cell lymphoma 2 inhibitor venetoclax. We provide a comprehensive analysis of key safety measures and efficacy in 342 patients comparing age categories ≥75 and <75 years treated in the relapsed, refractory non‐trial setting. We demonstrate that venetoclax has equivalent efficacy and safety in relapsed/refractory CLL patients who are elderly, the majority of whom are previous ibrutinib‐exposed and therefore may otherwise have few clear therapeutic options.